The Effect of Financial Reporting Quality on Regional Governments’ Performance Accountability - Agung, Mulyo (KnE Social Sciences, 2020)
Accountability is an important issue in Indonesian government. The present study aims to further analyze the performance accountability issue in regional governments in Indonesia, which is affected by the quality of financial reports. The fact shows that regional governments in Indonesia have low performance accountability. This study attempts to attest for or against the statement through testing whether or not financial reporting quality has an effect on regional governments’ performance accountability. Subjects of the study are 40 Satuan Kerja Perangkat Daerah (SKPD/Regional Government’s Work Units) of Regencies/Cities in Indonesia. Survey is the research methodology implemented. Hypothesis is analyzed and tested using Structural Equation Model (SEM). The findings show that good Financial Reporting Quality will improve Performance Accountability of regional governments in Indonesia, with a positive path coefficient. Keywords: Financial Reporting Quality, Regional Government’s Performance Accountability